Counties not countries: Variation in host specificity among populations of an aphid parasitoid - Keith R. Hopper (Evolutionary Applications, 2019)
AbstractParasitic wasps are among the most species‐rich groups on Earth. A major cause of this diversity may be local adaptation to host species. However, little is known about variation in host specificity among populations within parasitoid species. Not only is such knowledge important for understanding host‐driven speciation, but because parasitoids often control pest insects and narrow host ranges are critical for the safety of biological control introductions, understanding variation in specificity and how it arises are crucial applications in evolutionary biology. Here, we report experiments on variation in host specificity among 16 populations of an aphid parasitoid, Aphelinus certus. We addressed several questions about local adaptation: Do parasitoid populations differ in host ranges or in levels of parasitism of aphid species within their host range? Are differences in parasitism among parasitoid populations related to geographical distance, suggesting clinal variation in abundances of aphid species? Or do nearby parasitoid populations differ in host use, as would be expected if differences in aphid abundances, and thus selection, were mosaic? Are differences in parasitism among parasitoid populations related to genetic distances among them? To answer these questions, we measured parasitism of a taxonomically diverse group of aphid species in laboratory experiments. Host range was the same for all the parasitoid populations, but levels of parasitism varied among aphid species, suggesting adaptation to locally abundant aphids. Differences in host specificity did not correlate with geographical distances among parasitoid populations, suggesting that local adaption is mosaic rather than clinal, with a spatial scale of less than 50 kilometers. We sequenced and assembled the genome of A. certus, made reduced‐representation libraries for each population, analyzed for single nucleotide polymorphisms, and used these polymorphisms to estimate genetic differentiation among populations. Differences in host specificity correlated with genetic distances among the parasitoid populations.